Litterära värdeförhandlingar efter författarens död - Forslid, Torbjörn; Helsing, Daniel; Ohlsson, Anders (Tidskrift för litteraturvetenskap, 2025)
Negotiations of literary value and the death of the author In this article, we examine how the death of an author affects the value negotiation surrounding his or her oeuvre. As Barbara Herrnstein Smith has argued, literary value is not a fixed category but rather something that is created and negotiated in relation to various contexts and settings. For a high evaluation of the oeuvre of a given author – or a particular work – to be maintained, this value needs to be continuously repeated or ‘made’. By publishing books, appearing in legacy and social media, and so on, the author is one of the most central actors in the negotiation of literary value. This also means that the author’s death is a critical point in the value negotiation process. In this article, we examine the impact of the death of an author on the negotiation of literary value in the case of three Swedish authors: Sven Delblanc (1931–1992), Per Olov Enquist (1934–2020), and Kristina Lugn (1948–2020). We use data from three different databases, which provide different perspectives on the tendencies we are interested in examining: Artikelsök, Mediearkivet, and Sweden’s official library statistics. Our investigation shows that the media traffic surrounding these authors is clearly affected – and tends to decrease – after or in conjunction with the author’s death. The same tendency applies to library loans. For an author’s oeuvre to continue to be valued highly after the author’s death, it is necessary for other value agents/actors, for instance literary societies, biographers, etc, to step in and continue the negotiation of literary value. Through this process, some authors are eventually established as canonical. However, most authors slip into oblivion. This is a natural and necessary development, making it possible for new authors to enter the literary field.